Short-term very high carbohydrate diet and gut-training have minor effects on gastrointestinal status and performance in highly trained endurance athletes - King, A. J.; Etxebarria, N.; Ross, M. L.; Garvican-Lewis, L.; Heikura, I. A.; McKay, A. K. A.; Tee, N.; Forbes, S. F.; Beard, N. A.; Saunders, P. U.; Sharma, A. P.; Gaskell, S. K.; et al. (Nutrients, 2022)
We implemented a multi-pronged strategy (MAX) involving chronic (2 weeks high carbohydrate [CHO] diet + gut-training) and acute (CHO loading + 90 g·h-1 CHO during exercise) strategies to promote endogenous and exogenous CHO availability, compared with strategies reflecting lower ranges of current guidelines (CON) in two groups of athletes. Nineteen elite male race walkers (MAX: 9; CON:10) undertook a 26 km race-walking session before and after the respective interventions to investigate gastrointestinal function (absorption capacity), integrity (epithelial injury), and symptoms (GIS). We observed considerable individual variability in responses, resulting in a statistically significant (p < 0.001) yet likely clinically insignificant increase (? 736 pg·mL-1) in I-FABP after exercise across all trials, with no significant differences in breath H2 across exercise (p = 0.970). MAX was associated with increased GIS in the second half of the exercise, especially in upper GIS (p < 0.01). Eighteen highly trained male and female distance runners (MAX: 10; CON: 8) then completed a 35 km run (28 km steady-state + 7 km time-trial) supported by either a slightly modified MAX or CON strategy. Inter-individual variability was observed, without major differences in epithelial cell intestinal fatty acid binding protein (I-FABP) or GIS, due to exercise, trial, or group, despite the 3-fold increase in exercise CHO intake in MAX post-intervention. The tight-junction (claudin-3) response decreased in both groups from pre- to post-intervention. Groups achieved a similar performance improvement from pre- to post-intervention (CON = 39 s [95 CI 15-63 s]; MAX = 36 s [13-59 s]; p = 0.002). Although this suggests that further increases in CHO availability above current guidelines do not confer additional advantages, limitations in our study execution (e.g., confounding loss of BM in several individuals despite a live-in training camp environment and significant increases in aerobic capacity due to intensified training) may have masked small differences. Therefore, athletes should meet the minimum CHO guidelines for training and competition goals, noting that, with practice, increased CHO intake can be tolerated, and may contribute to performance outcomes.